Strategi Pengembangan Mufradat Bahasa Arab dalam Pembelajaran Kontemporer - Afiyatul Mardiyah; Ainur Rofiq Sofa (Lembaga Pengembangan Kinerja Dosen, 2025)
This article aims to identify and analyze strategies for developing Arabic vocabulary (mufradat) in the context of contemporary language learning. Mastery of vocabulary is a key pillar in language skills, encompassing listening, speaking, reading, and writing abilities. Challenges in teaching Arabic today include low student motivation, limited learning media, and a lack of contextual and innovative approaches. Therefore, adaptive strategies are needed to meet the demands of modern times and technology. This research uses a qualitative approach with a library research method, analyzing various scholarly sources such as journals, books, and research reports from the last fifteen years. The study reveals that effective strategies for vocabulary development include the use of interactive digital media, thematic approaches, project-based learning, and cooperative learning. The validity of these findings is reinforced through triangulation of sources and theories. Proper integration of these strategies has been proven to enhance vocabulary acquisition, student motivation, and active engagement in the Arabic language learning process. This study is expected to serve as a reference for educators, curriculum developers, and researchers in designing more effective and contextual vocabulary learning.